The Role of Talent Management in Achieving Competitive Advantage "A Field Study on a Sample of Employees at the Social Security Fund - West Benghazi" (Comprehensive Journal of Science, 2025)
The study aimed to know the level of talent management, in addition to identifying the level of competitive advantage and identifying the role of talent management in achieving competitive advantage in the Social Security Fund in the city of Benghazi. The researchers also followed the descriptive analytical approach, and used the questionnaire as a means of collecting the necessary data. The study community was represented by all workers, which amounted to (170) workers. To determine the sample size, the table of Krejcie and Morgan (1970) was relied upon, where its size was determined by the number of (118) individuals who were chosen by the simple random sample method. After distributing the questionnaire, (99) valid forms were retrieved for statistical analysis. To analyze the study data, the computer was used and a statistical program was used from the software service included in (SPSS). The study reached many results that can be summarized as follows : The study showed that the level of talent management had a medium relationship with the competitive advantage. In addition, the study revealed that there is a medium practice of talent management in the Social Security Fund under study. The study also concluded that there is a statistically significant effect of talent management with the competitive advantage at a statistical significance level of (0.05). Finally, the study presented a set of recommendations that are hoped to be followed and may contribute to enhancing the competitive advantage of the Social Security Fund.